The multidimensional logistic model according to the forecast of employment of graduates of institutions of higher education of the Republic of Kazakhstan - Laura A. Khassenova; Altyn M. Yessirkepova; M. K. Sejdachmetov; Zarema A. Bigeldiyeva; Dinmukhamed S. Zhakipbekov (Economies, 2023)
This article constructs a multidimensional logistic model for predicting the employment of graduates of higher educational institutions trained under the program of academic mobility, using the example of Kazakh universities. The purpose of the research is to identify the relationship between academic mobility and the employment of university graduates, as well as the necessary skills and competencies that can promote academic mobility in higher education institutions. This paper presents the results of calculating correlation coefficients and conducting a chi-square test, which demonstrated a relationship between the dependent variable and other questions in the graduate questionnaire. After the discovery of pairwise relationships, a multivariate logistic model was built that included statistically significant categories of responses. As a result, it was determined that the usefulness of participation in the academic mobility program is influenced by foreign language proficiency, an increase in academic mobility, the development of educational programs based on the needs of the labor market, as well as an increase in the weight of those methods that form practical skills in information analysis and the creation of public spaces in the labor market. The model demonstrated good predictive properties, which can be used to predict those individuals who were helped by academic mobility in finding employment.
Keywords: A02; C02; E01; I02; J06; 330; economics; academic mobility; employment of graduates; multidimensional model; correlation